Yield benefit and soil fertility improved by different fertilizer application placements and supplementary organic manure in Maize (Zea mays L.) - Jing Chao Yuan; Jian Zhao Liu; Wei Fan; Yao Liang; Song Cheng; Shui Mei Zhang; Chang Zhang; Jun Ren; Hong Guang Cai (Scientia Agricola, 2024)
ABSTRACT Through a long-term micro-area positioning experiment (2006-2017), the precise fertilization locations of spring maize (Zea mays L.) in Jilin, China, were investigated using an embedded cement bucket pot. The effects of different fertilization placements and additional application of organic manure on maize yield, biomass, grain nutrient uptake, and soil fertility were examined. Six treatments were designed: base fertilizer + topdressing shallow application (BF1TD1); base fertilizer deep + topdressing shallow application (BF2TD1); base fertilizer + topdressing deep application (BF1TD2); base fertilizer deep + topdressing deep application (BF2TD2); base fertilizer + topdressing + organic manure shallow application (BF1TD1 + OS); and base fertilizer + topdressing shallow application + organic manure deep application (BF1TD1 + OD). After 12 years of continuous experimentation, the findings revealed that BF2TD2, BF1TD1 + OS, and BF1TD1 + OD exhibited 10.59 %, 25.17 %, and 29.34 % higher average yields than BF1TD1, respectively. Deep topdressing was more beneficial in increasing maize yield and nutrient accumulation, and additionally, increasing the use of organic fertilizer enhanced plant biomass and nutrient uptake. Over the 12 years considered, the soil organic matter in the 0-20 cm and 20-40 cm layers increased by 45.96 % and 80.61 %, respectively, and the soil pH increased from 0.38 to 0.48. In general, the deep application of organic manure was more beneficial for soil retention as it can increase soil fertility in the 0-40 cm layer. Considering the high yield and nutrient absorption and utilization of maize, technical advancement for soil fertilizer in whole-field tillage layers was crucial.